Analisis Penggunaan Media Assemblr Edu Terhadap Hasil Belajar Siswa Kelas VB SDN Serang 03 - Nabilla, Elsa Rosania; Hidayat, Amat; Mubarok, Ahmad (Universitas Muhammadiyah Magelang, 2025)
This research is motivated by the need for innovative learning media that can address the challenges of 21st-century learning, particularly in making learning engaging, meaningful, and contextual. This research employed a descriptive qualitative methodology that employed observation, interviews, and documentation to collect data. The results showed that the use of Assemblr Edu had a positive impact on students' learning progress in several aspects, namely cognitive, affective, and psychomotor. Features such as 3D visualization and Augmented Reality (AR) in this application facilitated students' understanding of science material, improved memory, and made the learning process more enjoyable and less boring. Students also demonstrated a high enthusiasm for learning, were interested in creating their own learning aids, and were able to overcome technical problems that arose. In addition, Assemblr Edu's clear and uncluttered visual design made students feel comfortable while learning. The conclusion of this study indicates that Assemblr Edu is suitable for use as a learning medium in elementary schools. This tool is able to create a deep learning experience because Assemblr Edu media can make learning more enjoyable (joyful) and meaningful (meaningful). This media also has a real impact in encouraging changes in digital learning that can be adapted to the needs and characteristics of today's students.